Biosynthesized ZnO and MnO nanoparticles from Aegle marmelos peel extract for alkylphenol removal in wastewater - Pouya Karami; Mazeyar Parvinzadeh Gashti; Narges Fereydouni; Alessandro F Martins (Results in Chemistry)
Alkylphenols are persistent environmental contaminants that are difficult to remove using conventional water treatment methods. This study investigates the effectiveness of biosynthesized zinc oxide (ZnO) and manganese oxide (MnO) nanoparticles, synthesized using Aegle marmelos fruit peel extract, in the removal of alkylphenols from wastewater. The nanoparticles were characterized using Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) analysis, and particle size distribution measurements. The alkylphenol removal efficiency was tested under varying conditions such as time, concentration, nanoparticle dose, pH, and temperature. The concentration of alkylphenol was measured at 450 nm, and statistical analysis was performed using independent sample t-tests (p < 0.05) to compare the removal performance of MnO and ZnO nanoparticles. Results showed that MnO nanoparticles consistently outperformed ZnO in terms of removal efficiency across all conditions. XRD analysis confirmed the synthesis of ZnO and MnO nanoparticles, with ZnO exhibiting a hexagonal wurtzite structure and MnO showing a cubic phase. SEM revealed that MnO nanoparticles were spherical, while ZnO was irregular. The optimal removal conditions were observed at pH 5 and higher temperatures. Adsorption isotherm modeling further demonstrated that MnO had a higher adsorption capacity and stronger affinity for alkylphenol, making it a more effective material for wastewater treatment. This study highlights MnO nanoparticles as a superior alternative for the removal of alkylphenols from wastewater.